Impact of digital exposure on premarital sex and contraception use among unmarried Indian youth - Pragati Dattatraya Ubale; Punit Mishra; Aditi; Rajib Acharya; T.V. Sekher (Contraception and Reproductive Medicine)
Abstract Background Premarital sex in India is hugely stigmatized. With the widespread use of mobile phones and the internet, attitudes and behaviors towards premarital sexual activities are inevitably shifting. This study investigates the impact of digital exposure, specifically mobile phones and the internet on premarital sex and contraception use among unmarried Indian youths. Methodology Utilizing data from the 5th National Family Health Survey, the analysis includes 172,568 women and 33,397 men aged 15–29 years. The study applies univariate, bivariate, and multivariate statistical methods, such as Chi-square tests and Multiple Logistic Regression. Propensity Score matching addresses selection bias, estimating the impact of digital exposure on premarital sexual activities and condom use. Results The findings show that youth exposed to mobile phones and the internet are more likely to engage in premarital sex and use condoms during their first sexual encounter. Specifically, 13.46% of men and 2.83% of women reported premarital sex, with 60.84% of men using condoms at first sex. These behaviors are significantly associated with age, education, urban residence, and mass media exposure. Conclusion Digital exposure significantly influences premarital sexual behaviors and contraception use among unmarried Indian youth. Adoption of mobile devices and internet usage in India should be accompanied by the implementation of holistic and culturally appropriate technology-driven interventions to provide sex education in India.